2003
DOI: 10.1034/j.1399-0012.2003.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcineurin inhibitors on endothelial function in renal transplant recipients

Abstract: Endothelial dysfunction is of vital importance, as it may cause ischemia and dysfunction in various organs. Despite, this problem has been well documented in patients with end-stage renal disease (ESRD), there is not enough data considering this issue following renal transplantation. One of the potential causes of endothelial dysfunction in renal transplant recipients may be administration of calcineurin inhibitors. The aim of this study is to evaluate the effects of two different calcineurin inhibitors [cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…The study design did not allow to compare the effects of cyclosporine A- and tacrolimus-based regimes. Earlier data suggest that calcineurin inhibitors induce endothelial dysfunction in renal transplant patients, probably by suppressing NO synthesis [32,33]. However, according to our results, ADMA levels were significantly higher in obese patients after renal transplantation, although the immunosuppression regimens were similar in both groups.…”
Section: Discussionsupporting
confidence: 51%
“…The study design did not allow to compare the effects of cyclosporine A- and tacrolimus-based regimes. Earlier data suggest that calcineurin inhibitors induce endothelial dysfunction in renal transplant patients, probably by suppressing NO synthesis [32,33]. However, according to our results, ADMA levels were significantly higher in obese patients after renal transplantation, although the immunosuppression regimens were similar in both groups.…”
Section: Discussionsupporting
confidence: 51%
“…These findings suggest that, unlike conventional immunosuppressive drugs, FTY720 may preserve vascular structure and function and help prevent cardiovascular morbidity and mortality that often occurs in transplant recipients. 18,19 …”
mentioning
confidence: 99%
“…In this study, CsA caused some detrimental effects on capillary morphology and resulted in a significant increase in capillary ET-1 release, while TAC did not [66] . Furthermore, CsA yielded a greater impairment in brachial endothelial function using high resolution vascular ultrasound in renal transplant patients, compared with TAC treated patients [67] . Additionally, in another clinical study comparing the effects of both CNIs on endothelial function, ET-1 levels and vascular remodeling in CTx patients, the investigators reported that microvascular endothelial function was worst, concomitantly with higher ET-1 plasma levels, and a larger increase in coronary intimal area in CsA-treated patients [63] .…”
Section: Impact Of Immunosuppressive Regimens On Cavmentioning
confidence: 90%